2018
DOI: 10.1137/17m1159294
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing Movements for Mean Curvature Flow of Partitions

Abstract: Under suitable assumptions on the family of anisotropies, we prove the existence of a weak global 1 n+1 -Hölder continuous in time mean curvature flow with mobilities of a bounded anisotropic partition in any dimension using the method of minimizing movements. The result is extended to the case when suitable driving forces are present. We improve the Hölder exponent to 1 2 in the case of partitions with the same anisotropy and the same mobility and provide a weak comparision result in this setting for a weak a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 97 publications
(223 reference statements)
1
9
0
Order By: Relevance
“…In this section we prove density estimates for almost minimizers (see theorem 3.2). In the two-phase case without mobility, density estimates have been proven in [1,42] (see also the proof of theorem 4.2 for the case with mobility and forcing) and in the isotropic N -phase case is proven in [14]. The proof of theorem 3.2 is similar to [14, theorem 3.6], however, some (technical) difficulties arise when two anisotropies differ too much and this is why we need assumption (3.5) for proving the lower-density estimates.…”
Section: Density Estimates For Almost Minimizersmentioning
confidence: 95%
See 2 more Smart Citations
“…In this section we prove density estimates for almost minimizers (see theorem 3.2). In the two-phase case without mobility, density estimates have been proven in [1,42] (see also the proof of theorem 4.2 for the case with mobility and forcing) and in the isotropic N -phase case is proven in [14]. The proof of theorem 3.2 is similar to [14, theorem 3.6], however, some (technical) difficulties arise when two anisotropies differ too much and this is why we need assumption (3.5) for proving the lower-density estimates.…”
Section: Density Estimates For Almost Minimizersmentioning
confidence: 95%
“…The following volume-distance comparison appeared in a similar form also in [1,14,42] and will be used in the proof of the existence of GMM.…”
Section: By (25) (24) and The Essential Disjointness Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Chambolle [9] showed that the scheme [2,25] which seems academic at a first glance can be implemented rather efficiently. Recently, Bellettini and Kholmatov [6] analyzed the scheme in the multi-phase case. However, neither a conditional convergence result to a distributional BV-solution, nor one to a Brakke flow are available yet.…”
Section: Introductionmentioning
confidence: 99%
“…Such time-discrete schemes have been used in the study of geometric evolutions starting from the pivotal works by Almgren, Taylor and Wang [2] and by Luckhaus and Sturzenhecker [23] in the case of the mean curvature flow. An extension of these techniques to multiple-phase systems can be found in [4], while an adaptation to the L 2 -gradient flow for the elastic energy (p = 2) of an open curve, which gives rise to a fourth order flow, has been recently proposed in [13,3].…”
Section: Introductionmentioning
confidence: 99%